(untitled) (Bioscience Journal, 2020)
This work evaluated the antifungal activity of essential oils of Myrcia ovata chemotypes (MYRO-175, MYRO-156, MYRO-154, MYRO-165, and MYRO-015) and their major compounds (linalool, geraniol, citral, and (E)-nerolidol) on the phytopathogenic fungi Fusarium pallidoroseum (which causes melon postharvest rot) and Colletotrichum musae (which causes anthracnose in banana). The essential oils were obtained by hydrodistillation and analyzed by GCMS/FID. To evaluate the antifungal activity, the essential oils and their major compounds were tested at different concentrations (0.1; 0.3; 0.4; 0.5; 0.7; 1.0; 3.0, and 5.0 mL/L). The major compounds found in the essential oils were nerolic acid, linalool, geraniol, citral, and (E)-nerolidol. The essential oils of the plants MYRO-154, MYRO-165, and MYRO-015 had the minimum inhibitory concentration (MIC) (0.3 mL/L) for F. pallidoroseum and the lowest minimum fungicidal concentration (MFC) (0.7 mL/L), for C. musae. Geraniol and citral had the lowest MFC (0.5 mL / L) for the two fungi tested. For F. pallidoroseum, the essential oils of the chemotypes were more effective than their major compounds. Conversely, the major compounds geraniol of the chemotype MYRO-156 (74.37%) and citral were more effective than their respective essential oils for C. musae. (E)-nerolidol and geraniol of the chemotype MYRO-015 (33.15%) were responsible for the antifungal activity of the essential oils of their respective chemotypes.